Economic analysis of combating aeges aegypti in Brazil according dynamic efficiency perspective - Sousa, Thiago de Castro; Paranaiba, Adriano de Carvalho (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2017)
This paper intends to identify the features of an economic environment that is conducive to the development of efficient solutions in the fight against Aedes aegypti mosquito in Brazil. A brief history of governmental efforts to eradicate the vector is told, highlighting the recent ban on Dichloro-Diphenyl-Trichloroethane (DDT), followed by a theoretical analysis of so-called market failures and government failures. The concept of “Dynamic Efficiency”, according to the theories of Kirzner and Huerta de Soto, was used to support the thesis that greater social gains may be accomplished by fighting the contagious vector in an environment of strong respect for private property and voluntary agreements.